anxiety THE RELATIONSHIP BETWEEN ANXIETY DISORDER AND PANIC ATTACK TOWARD FINAL YEAR STUDENTS AT STIKES BULELENG: reducing level anxiety - Nur Rinasari; Agus Ari Pratama; I Ketut Pasek; Made Yos Kresnayana (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2023)
Introduction: Anxiety disorder or anxiety disorder is an individual's condition in which persistent fear is difficult to control. Panick attack or panic attack is a condition of panic attack that no one expects. Panic attacks often cause excessive fear and possible recurrence, which also affects changes in individual behavior in everyday life. Students in the course of scripting face a variety of psychological disorders such as stress, depression, and frequent anxiety. Method: The research design used in this study is a cross sectional approach. The population in this study is all final-level students at STIKes Buleleng,. The sample size used was 70 respondents selected using random sampling techniques. Data collection techniques using the DASS questionnaire. Result: the results of a statistical chi square test of this study show a p-value = 0.000 which is 00.05 so that it can be interpreted that there is a relationship between Anxiety Disorder and Panic Attack of End-Level Students at STIKes Buleleng. Conclusion: there is a relationship between Anxiety Disorder and Panic Attack at STIKes Buleleng towards final year students who are preparing their thesis.